Impact of Humin on Soil Adsorption and Remediation of Cd(II), Pb(II), and Cu(II). Issue 6 (17th August 2016) - Wang, Yahui; Li, Liming; Zou, Xuegang; Shu, Ranjun; Ding, Ling; Yao, Kun; Lv, Wenying; Liu, Guoguang
ABSTRACT: In situ immobilization constitutes a promising technology for the mitigation of contaminants, through the reduction of metal bioavailability and mobility. This study investigated the adsorption isotherms and kinetic characteristics of humin extracted from peat soils. We also studied the influences of the pH, ionic strengths, and soluble organic matter concentrations of soil solutions on the adsorptive properties of humin, and compared its ability to detoxify potentially toxic metals in both actual and simulated soil solutions. The study results indicated that humin contains a massive population of oxygen-containing functional groups. Its adsorption capacity for Pb(II) was greater than that for Cu(II), which exceeded that for Cd(II). The adsorption of humin for Pb(II) conformed to the Freundlich model, while the adsorption of humin for Cd(II) and Cu(II) followed the Langmuir model. The adsorption kinetics of humin with respect to potentially toxic metals aligned well with second-order kinetics equations. As the pH was elevated, the potentially toxic metal adsorption by humin increased rapidly. Electrolyte ions and tartaric acids in solution both inhibited the adsorption of potentially toxic metals by humin, and its ability to inactivate potentially toxic metals. This was shown to be improved in actual field soil solutions in contrast to simulated soil solutions.